Precise measurements of the decay of free neutrons - Dubbers, Dirk; Märkisch, Bastian (Annual review of nuclear and particle science, 2021)
The impact of new and highly precise neutron \b{eta} decay data is reviewed. We focus on recent results from neutron lifetime, \b{eta} asymmetry, and electron-neutrino correlation experiments. From these results, weak interaction parameters are extracted with unprecedented precision, possible also due to progress in effective field theory and lattice QCD. Limits on New Physics beyond the Standard Model derived from neutron decay data are sharper than those derived from high-energy experiments, except for processes involving right-handed neutrinos.